Environmental factors associated with gastric carcinogenesis. Issue 2 (28th March 2022) - Kayamba, Violet; Kelly, Paul
Abstract : Purpose of review: Gastric cancer is one of the leading causes of cancer-related deaths globally. Several modifiable environmental factors have been linked to gastric carcinogenesis but in many cases, evidence is either weak or fragmented. In this review, we interrogate the latest evidence implicating environmental factors in the development of gastric cancer. Recent findings: We are writing this review at a time when technological advancements are enabling scientists to effectively conduct large epidemiological studies with better tools for exposure estimations. We have highlighted risk factors that do not yet have enough evidence to be included as definite carcinogens in the International Agency for Research on Cancer monographs but have the potential for inclusion in the near future. Considered in our review are the links between gastric cancer and exposure to biomass smoke, particulate matter, occupational hazards and water contamination. Summary: This review illustrates the need for vigilance as evidence linking gastric cancer to various environmental factors is mounting. Many of these factors are modifiable, allowing for preventive strategies that could further decrease the global burden of gastric cancer.